O Letramento literário no processo de alfabetização na Rede Municipal de Educação de Senador Canedo-GO - (:unkn) unknown (Universidade Estadual de Goiás, 2025)
This research is part of the line of research on Language and Social Practices in the area of Educational Processes, Languages, and Technologies from the Interdisciplinary Graduate Program in Education, Language, and Technologies. The research is based on themes that permeate Literary Literacy in the literacy process, such as the concept of Literary Literacy, the school space with its disarticulations, and the literacy process. The study presents the following problematizing question: What are the interferences of Literary Literacy in the literacy process in the municipal education network of Senador Canedo-GO? To this end, the research aims to understand the interferences of Literary Literacy in the literacy process in the municipal education network of Senador Canedo-GO. This study relies on UEG - Câmpus Anápolis de Ciências Socioeconômicas e Humanas Programa de Pós-Graduação Interdisciplinar em Educação, Linguagem e Tecnologias (PPG-IELT) Av. Juscelino Kubitschek, 146 - Jundiaí - Anápolis-GO - CEP 75110-390 Fone: (62) 3328-1188 E-mail: ppgielt@ueg.br Homepage: www.ppgielt.ueg.br analyzing the programs Tempo de Aprender from the Federal Government, AlfaMais Goiás from the State Government, and the Municipal Education Plan of Senador Canedo (PME). The research deepens this understanding through the reflective analyses of the “Storytelling Guide” (Brasil, 2021), which is part of the federal program Tempo de Aprender, and two literary books that make up the literary kits of the state program AlfaMais Goiás. Methodologically, it uses a qualitative approach; as to the objectives, it is exploratory and is close to Phenomenology. As for the procedures, the research is bibliographic, bibliographic research with a documentary basis, and is characterized as a case study. Concerning Literary Literacy, the research is based on Cosson (2022), Todorov (2009), and Gutfreind (2020). Regarding the documentary analyses, the Tempo de Aprender, Alfa Mais Goiás digital platforms, and PME programs were used. The results of the analyses expose the absence of actions, projects, financial resources, and awareness. In addition, the importance of Literary Literacy in the literacy process is observed due to the potential to awaken the pleasure of reading in the child, becoming essential for the formation of a new generation, which, when reading, reflects, questions, elaborates new conceptions and acts in an emancipatory way in the context in which it lives.
Literacy in the literacy process in the Municipal Education Network of Senador Canedo-GO
Keywords: Letramento Literário - Senador Canedo; Processo de Alfabetização - Senador Canedo; Literary Literacy - Senador Canedo; Literacy process - Senador Canedo; CIENCIAS HUMANAS::EDUCACAO